Desain Perancangan Alat Penyaring Dalam Proses Pembuatan Tahu Dengan Metode Macro Ergonomic Analysis and Design (MEAD) - Angga Haripurna; Hari Purnomo (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2017)
Gunung Kidul Regency is a region of soybean producer in Daerah Istimewa Yogyakarta. The raw materials support the tofu-making industry where one of the centers of tofu industry in Siraman and Sumbermulyo Wonosari. The productivity of the tofu manufacturing process is determined on the work tool and worker performance. To increase productivity a holistic approach is necessary considering all aspects. In this research, the method used to design holistically is macro ergonomic analysis and design (MEAD). With a sociotechnical MEAD approach, it is identified control variance to avoid musculoskeletal complaints that have an impact on increased productivity. This research only makes the design with high tool filter is 1014,70 mm and width 419,9 mm. A blower tool that facilitates removal of soy water material with suction specification and press 30 m / s using 220 VA power supply and 1300 VA power with galvanized pipe as conductor of 2 inch diameter.